“Quis voar a uma alta torre”: para uma leitura hubrística de The Spire (1964), de William Golding - Alarcão, Miguel (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2020)
The mental spatializations or topographies that we construct, if only unconsciously, tend to place God, Heaven and Good in the heights and hence the Devil, Hell and Evil in the depths; we are, however, unaware of any specific studies and bibliographies on this issue pertaining theological and moral representation(s). As far as medieval religious architecture from (and since) the 12th century is concerned, this view materializes in the idea that the verticalism associated with the Gothic style (or mode) was a way of lifting and leading spiritually unto God the soul, the mind and the heart of the believers. This brief introductory note seeks to present the novel The Spire (1964), by Sir William Golding, awarded The Booker Prize (1980) and The Nobel Prize for Literature (1983).